You can plug -x - 1 for y in the first equation
2x - (-x - 1) = 10
2x + x + 1 = 10
Combine
3x = 9
Divide
x = 3
Plug 3 for x in any equation ( I'll use th second equation )
y = - (3) - 1
y = - 3 - 1 = -4
x = 3 ; y = -4
(3, -4)
A) 1.15
B) 2.87
C) 3.59
D) 4.22
E) 5.74
F) 6.95
G) 7.25
H) 8.64
I) 9.68
J) 28.33
Answer:
9
Step-by-step explanation:
25-7=18
half of 18 is 9
Hope this helps you understand
Answer:
198.6 with the remaining 6
Step-by-step explanation:
596/3
596/3 = 198.666666667 as a decimal form
596/3 = 198.67 in 2 decimal places
596/3 = 198.7 to the nearest tenth
596/3 = 198.67 to the nearest hundredth
596/3 = 198.667 to the nearest thousandth